2002
DOI: 10.1063/1.1483390
|View full text |Cite
|
Sign up to set email alerts
|

60Co gamma-irradiation-induced defects in n-GaN

Abstract: Transient capacitance measurements of Schottky diodes fabricated on nominally undoped n-type GaN exposed to 60Co gamma irradiation indicate the introduction of two defect levels with thermal activation energies of 89±6 and 132±11 meV. While the emission characteristics of these defects manifest significant broadening, their parameters are consistent with reported electron-irradiation-induced nitrogen-vacancy related centers. Three deep-level defects present before irradiation exposure with activation energies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 13 publications
1
39
0
Order By: Relevance
“…179 The defect peaks showed significant broadening, but were consistent with electron-irradiationinduced nitrogen-vacancy related centers. 179 Neutron damage.-Fast neutron irradiation with fluxes > 10 15 cm −2 caused degradation in the I-V characteristics as well as light output of blue GaN LEDs emitting at 476 nm. 174 Atomic displacements were reported as responsible for both of the electrical and optical degradations.…”
Section: Radiation Damage In Ingan/gan Light Emitting Diodesmentioning
confidence: 83%
See 1 more Smart Citation
“…179 The defect peaks showed significant broadening, but were consistent with electron-irradiationinduced nitrogen-vacancy related centers. 179 Neutron damage.-Fast neutron irradiation with fluxes > 10 15 cm −2 caused degradation in the I-V characteristics as well as light output of blue GaN LEDs emitting at 476 nm. 174 Atomic displacements were reported as responsible for both of the electrical and optical degradations.…”
Section: Radiation Damage In Ingan/gan Light Emitting Diodesmentioning
confidence: 83%
“…178 Transient capacitance measurements of Schottky diodes fabricated on undoped n-type GaN exposed to 60 Co gamma irradiation indicate the introduction of two defect levels with thermal activation energies of 89 and 132 meV. 179 The defect peaks showed significant broadening, but were consistent with electron-irradiationinduced nitrogen-vacancy related centers. 179 Neutron damage.-Fast neutron irradiation with fluxes > 10 15 cm −2 caused degradation in the I-V characteristics as well as light output of blue GaN LEDs emitting at 476 nm.…”
Section: Radiation Damage In Ingan/gan Light Emitting Diodesmentioning
confidence: 97%
“…The ET1(E c À(0.06-0.090) eV) traps were first reported for electron and gamma-irradiated samples [192][193][194] and are believed to be nitrogen vacancy donors [192]. The ET2 and ET3 electron traps near E c À(0.12-0.14) eV and E c À(0.16-0.18) eV were observed in gamma-irradiated [193,194], electron irradiated [13,16,195] or proton irradiated n-GaN [196][197][198][199] (see Refs.…”
Section: Deep Traps In Ganmentioning
confidence: 99%
“…The lower energy was related to V N defects while the higher energy was possibly due to coupled neighboring defects. 17 The coupling of an interstitial and nearby vacancy is known as a Frenkel pair. These defects have been observed experimentally in GaN after being subjected to 0.7-1.0 MeV electron irradiation.…”
Section: Experiments and Theorymentioning
confidence: 99%
“…The activation energy revealed that for extended doses, the energy of the trap increaseddropped further below the conduction band -suggesting an increase in the population of defects which couple with nearby V N . 17 The increased density of deeper trap levels increases scattering leading to shorter L. The extended defects generated in the buffer layer can be responsible for changes in dc properties including increases in gate leakage current. 28,35 The effectiveness of annealing for gamma induced defect mitigation has been explored in Ref.…”
mentioning
confidence: 99%